ANALISIS BEBERAPA VARIABEL YANG MEMPENGARUHI TINDAK LANJUT TEMUAN AUDIT MANAJEMEN PADA FUNGSI KEUANGAN PERUSAHAAN DI BALIKPAPAN - Ernayani, Rihfenti (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
This research has purpose to test, and provide empirically evidences upon the influence of management support, internal communication, and internal control towards management audit follow up at Financial Function. This research is taking location in East Borneo Province, especially in Balikpapan, with the respondents of company’s directors, internal auditors, financial managers, and other functional managers in the company. The technique of sample taking applies simple random sampling, while data collection applies the distribution of 100 questionnaires, while only 66 out of them are returned. Data is analyzed by multiple linear regressive method. The research result shows that management support significantly affects to-, while both internal communication, and internal control do not affect to management audit follow up at financial function.